Fundamentos epistemológicos sobre la prueba en el proceso penal ecuatoriano bajo el prisma del derecho procesal contemporáneo - Hurtado Morocho, Danny Jonhatan (2016)
The production and evaluation of evidence in criminal proceedings based on Ecuadorian theoretical concepts capable of guiding the search for truth and its establishment in a full, objective, testable and based entirely, working as potential scientific hypotheses. The thesis of epistemological subjectivism that prevailed in the theoretical context doctrinal until the first half of the twentieth century and served as scientific support to European legislation in this period did not allow search and guide the establishment of the truth in criminal proceedings on an objective basis and so full, testable and grounded. The theoretical concepts upon which rests the search for truth and its establishment in the criminal Ecuadorian correspond to the thesis of epistemological subjectivism. This raises the importance of the ideas of epistemology that is made on the evidence in court. Validity is a subject that has to study, mainly the veracity of the proceedings, as the court in obtaining evidence and assessment has the potential to affect the person in all aspects of his life existential: the physical, the psychological and the social, which can also involve the violation of fundamental rights. On the other hand, the measure of effectiveness involves mainly to epistemological reflections of the truth about the facts. We analyze the correspondence truth as the ideal. It also discusses the concepts of truth consensual, coherent and pragmatists who have been hoisted as a denial of it. In their preparation, the validity of the test is related to due process. A formal validity refers to the conditions of legitimate bodies and the formalities of the time, place and manner of obtaining evidence and procedural material validity, which relates to the constitutional formality of content: the latter refers basically 5 that the judge's decision respects the principle of proportionality as well as the rationality of his argument on the facts as a condition of legitimacy of the decision. To enter the field of the process, we have to start from your home, dig then ask: what is the origin of the process? In this respect the process born by the need for states to resolve legal disputes, which essentially involves the breaking of the rules that the state imposes on the exercise of its legislative, administrative and judicial, is this conflict, which originates settlement forms, one of which is the process where the evidence is inserted, an issue that is the subject of this article, remember that in general, the test object the facts asserted by the parties in the process device but with the intervention of the judge as director, because the process is not party membership, but their forms are mandatory.